Issues of developing catering services in the region - Nasiba Ergasheva, (THE INNOVATION ECONOMY, 2026)
This article presents scientifically based proposals and recommendations on the priority areas of scientific research in this area, such as modern forms of organization and development of catering services in the region, the main trends in the global catering outsourcing services market and its geography, the importance, structure and specific characteristics of enterprises and organizations, criteria for qualitative assessment of the provision of all areas, directions for the development of catering services, innovative approaches to the organization of catering and the use of digital technologies